Increased interferon I signaling, DNA damage response and evidence of T-cell exhaustion in a patient with combined interferonopathy (Aicardi-Goutières Syndrome, AGS) and cohesinopathy (Cornelia de Lange Syndrome, CdLS) - Sorina Boiu; Nikolaos Paschalidis; George Sentis; Theodora Manolakou; Andrianos Nezos; Manolis Gialitakis; Maria Grigoriou; Erato Atsali; Melpomeni Giorgi; Argirios Ntinopoulos; Clio Mavragani; Periklis Makrythanasis; et al. (Pediatric Rheumatology Online Journal)
Abstract Background Type I interferonopathies including Aicardi-Goutiéres Syndrome (AGS) represent a heterogeneous group of clinical phenotypes. Herein, we present a Case with combined AGS and Cornelia de Lange Syndrome (CdLS)—a cohesinopathy—with comprehensive analysis of the immune and genomic abnormalities. Case and methods A 20-year old man presented with chilblain lesions and resorption of distal phalanges of fingers and toes, somatic and psychomotor retardation, microcephaly, synophrys, hearing losing and other aberrancies consistent with the phenotype of CdLS. We used whole exome sequencing to genetically map the associated mutations and performed transcriptome profiling and enrichment analysis in CD14+ monocytes of the patient and immune phenotyping by mass cytometry (CyToF), comparing to healthy individuals and lupus patients as disease controls. DNA damage response was assayed by confocal microscopy in the peripheral blood of this patient. Results Next generation exome sequencing confirmed a homozygous SAMHD1 gene mutation and a hemizygous non-synonymous mutation on SMC1A gene, responsible for the AGS and CdLS, respectively. Transcriptome profiling of CD14+ monocytes of the patient showed enrichment of type I IFN signaling and enhanced DNA damage response pathway. Broad immune phenotype of the peripheral blood of the patient revealed absence of activated T cell populations, increased frequency of NK cells and plasmablasts and enhanced granulocytic lineage. Further analysis suggested activation of the ATM branch of DNA damage response and increased apoptosis in the periphery of the patient. Conclusions A rare case of a patient bearing two genetic lesions (responsible for AGS/CdLS syndromes) exhibits distinctive features of genomic damage and interferon responses. Immune phenotype revealed granulocytic skewing and absence of activated T cells compatible with chronic antigenic stimulation and/or homing of these cells at sites of inflammation.